2023
DOI: 10.1021/acsomega.3c04205
|View full text |Cite
|
Sign up to set email alerts
|

Various Extraction Techniques of Curcumin─A Comprehensive Review

P. Sai Lakshmi Manasa,
Alka D. Kamble,
Ushasri Chilakamarthi

Abstract: Curcumin, the active component of the rhizome of Curcuma longa, is a safe substance whose applications are extensively used in medicinal, biological, pharmacological activities, and food cosmetic additives. In the field of medicine, curcuminoids have a greater impact; they have been associated with the suppression of neuropathic pain, depression, angiogenesis, tumorigenesis, diabetes, and diseases of the liver, skin, and pulmonary systems, as well as cardiovascular and nervous systems. These are in high demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Both resveratrol and curcumin are classified as supplements; the United States Federal FDA does not regulate these products. While this may be advantageous to some manufacturers as it eliminates the FDA regulatory burden, the lack of stringent regulations for supplements leads to considerable variations in formulations and concentrations of specific compounds in the product [133]. Our analysis using mass spectroscopy on five different commercially available resveratrol preparations revealed substantial disparities between the reported concentrations and the concentrations measured with mass spectroscopy.…”
Section: Lack Of Regulationmentioning
confidence: 84%
“…Both resveratrol and curcumin are classified as supplements; the United States Federal FDA does not regulate these products. While this may be advantageous to some manufacturers as it eliminates the FDA regulatory burden, the lack of stringent regulations for supplements leads to considerable variations in formulations and concentrations of specific compounds in the product [133]. Our analysis using mass spectroscopy on five different commercially available resveratrol preparations revealed substantial disparities between the reported concentrations and the concentrations measured with mass spectroscopy.…”
Section: Lack Of Regulationmentioning
confidence: 84%
“…The previous studies have demonstrated a broad variation in the extraction factor range. Maceration, also referred to as solid-liquid extraction or "soaking," is a commonly utilized and well-known method for extracting solvents from solid substances [25]. A study conducted by Yulianto et al obtained a higher EY of curcumin using a solid-to-liquid ratio of 0.1 g/mL [23].…”
Section: Selection Of Extraction Factors For Two-level Factorial Designmentioning
confidence: 99%
“…However, we did not come across no studies have employed a two-level factorial design to enhance the extraction of curcuminoid compounds from C. longa rhizomes. The previous research has demonstrated that various solid-to-liquid ratios, ethanol concentrations, and extraction times can be independently utilized to achieve satisfactory outcomes when attempting to extract curcuminoid compounds [2,15,[22][23][24][25][26]. To optimize the extraction process, we employed a two-level factorial design to determine the most effective combination of solid/liquid ratio, ethanol concentration, and maceration time for the extraction of curcuminoids from turmeric rhizomes.…”
Section: Introductionmentioning
confidence: 99%